The effect of triaxiality on finite element deletion strategies for simulating collapse of full-scale steel structures. (1st May 2020) - Saykin, Vitaliy V.; Nguyen, Tam H.; Hajjar, Jerome F.; Deniz, Derya; Song, Junho
Highlights: Two FE deletion strategies that account for fracture are compared and validated. Specific parameters' influence on performance of FE deletion strategies is discussed. FE deletion strategies that account for triaxiality have greatest degree of accuracy. Abstract: Collapse prediction of steel structures should incorporate a finite element model that accounts for ductile fracture through material separation in critical structural members. Finite element deletion approaches have been used successfully in the past to account for fracture in steel members. However, the current common approach in collapse modeling of steel structures, a constant critical strain strategy (CS), typically requires recalibration when used with different structural configurations due to the fact that it does not account for triaxiality, which is a primary parameter in ductile fracture. To better predict structural response of steel structures undergoing collapse, it is important to study the effect of triaxiality on fracture in steel structures. A new finite element deletion approach that accounts for triaxiality was previously proposed, calibrated, and validated in small steel specimens for use in predicting collapse of steel structures. In this approach, fracture initiation is modeled using Void Growth Model (VGM) and the subsequent softening of the material to element deletion is modeled by a Hillerborg model. This paper describes the change of triaxiality, equivalent plastic strain, and other parameters during the duration of the loading, influencing the strategies implemented and provides explanation for the performance shown. In addition, the paper examines the effect of triaxiality on accurately predicting fracture in steel structures through comparison of VGM to CS strategy with validation in simulations of full-scale structural steel connection and frame tests without recalibration. The VGM strategy provided an accurate prediction based on calibration to test results that are most widely available for different types of structural steels, while CS strategy frequently provided less accurate results. The VGM strategy thus allows for an accurate collapse modeling of steel structures for use by researchers, code developers, and practitioners who address collapse of steel structures.